Pemanfaatan Media Sosial Instagram sebagai Sarana Promosi TXTURE - Muhammad Rifqi Fakhruddin; Yulianti (UNISBA Press, 2023)
Abstract. The current business development makes several sectors in the fashion industry increase. Especially social media has an important role in making it easier for business people to promote and sell sales. One of the platforms described in this study is instagram, instagram is a platform that has a wide and large reach. as did the TXTURE brand where they use instagram as one of the promotional media by bringing out the uniqueness of the TXTURE brand. The purpose of this study is to determine the form of promotion, and to find out what factors are an obstacle for TXTURE. This study uses a qualitative research method with a case study approach formulated by Robert K Yin, where the method examines a case using the main questions